2017
DOI: 10.1111/acem.13217
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Intracranial Hemorrhage in Ground‐level Fall With Antiplatelet or Anticoagulant Agents

Abstract: There is a low incidence of clinically significant tICH with a ground-level fall in head trauma in patients taking an anticoagulant or antiplatelet medication. There was no statistical difference in rate of tICH between antiplatelet and anticoagulants, which is unanticipated and counterintuitive as most literature and teaching suggests a higher rate with anticoagulants. A larger data set is needed to determine if small differences between the groups exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 25 publications
5
46
1
Order By: Relevance
“…Although anticoagulation is often cited as a major risk factor for traumatic intracranial bleeding, we did not confirm that association. In this regard, our findings are similar to those published by Nishijima et al and Ganetsky et al and question the logic of ordering an ED head CT for older adults who have fallen, solely on the basis that they are on an anticoagulant.…”
Section: Discussionsupporting
confidence: 91%
“…Although anticoagulation is often cited as a major risk factor for traumatic intracranial bleeding, we did not confirm that association. In this regard, our findings are similar to those published by Nishijima et al and Ganetsky et al and question the logic of ordering an ED head CT for older adults who have fallen, solely on the basis that they are on an anticoagulant.…”
Section: Discussionsupporting
confidence: 91%
“…To date, specific recommendations are missing for low‐energy trauma in older patients such as ground‐level falls with or without anticoagulation or antiplatelet treatments and equivocal clinical signs of traumatic brain injury. Current studies on these particular patients are heterogeneous and bear some limitations, such as missing control group, small sample sizes, or lacking information about injury severity …”
mentioning
confidence: 99%
“…[6][7] However, some studies have not identified an increase in post fall ICH in this cohort and conclude that concerns regarding OAC agents are overstated. [8][9] Atrial fibrillation guidelines recommend anticoagulation for almost all older patients, 10-11 thus, physicians have a difficult choice: to provide OAC to minimize vascular risk while increasing the risk of ICH or vice versa. 2 Anticoagulation introduces complexity and cost to post-fall injury management.…”
Section: Discussionmentioning
confidence: 99%